2017
DOI: 10.1002/zaac.201700049
|View full text |Cite
|
Sign up to set email alerts
|

Pyridyl Containing 1,5-Diaza-3,7-diphosphacyclooctanes as Bridging Ligands for Dinuclear Copper(I) Complexes

Abstract: 1,5-bis(R)-3,7-bis[2-(pyridine-2Ј-yl)ethyl)-1,5-diaza-3,7-diphosphacyclooctanes 1 and 2 and their copper(I) complexes 3 and 4 were developed. The butterfly-shaped copper-iodide core and unusual P,N-chelate and P,P-bridged coordination mode of the heterocyclic ligand in the dinuclear complexes 3 and 4 were revealed. Complexes 3 895 and 4 display emission in green range of spectra, with lifetimes in a microsecond domain and quantum yields of luminescence in solidstate up to 38 %. Thermochromic effects found for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Our previous works demonstrated that N-aryl-substituted 1,5-diaza-3,7-diphosphacyclooctanes 1 and 2 are structurally preorganized for a bridging coordination of copper­(I) and gold­(I) cations. , The 1:1 reaction of ligands 1 and 2 with [AuCl­(tht)] (tht = tetrahydrothiophene) or AuI in acetone led to the formation of macrocyclic P,P-bridged bimetallic gold­(I) complexes 3 – 6 , respectively (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous works demonstrated that N-aryl-substituted 1,5-diaza-3,7-diphosphacyclooctanes 1 and 2 are structurally preorganized for a bridging coordination of copper­(I) and gold­(I) cations. , The 1:1 reaction of ligands 1 and 2 with [AuCl­(tht)] (tht = tetrahydrothiophene) or AuI in acetone led to the formation of macrocyclic P,P-bridged bimetallic gold­(I) complexes 3 – 6 , respectively (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the P,N-ligands used for the synthesis of heterometallic Au I /Ag I or Au I /Cu I complexes are the pyridine-2-ylphosphine and analogous phosphines with an N-heterocycle, where an N-heterocyclic group is directly connected toward a P-donor center. ,, Spatial distancing of the pyridyl group from the phosphorus coordination center opens the way to the principally different coordination properties. , Surprisingly, ligands, such as PyCH 2 PR 2 or Py­(CH 2 ) 2 PR 2 with spatial outlying of P- and N-donor centers, are not well studied concerning the synthesis of copper­(I) and gold­(I) complexes . Heterocyclic bisphosphines with exocyclic pyridylethyl groups are promising P,P- or P,N-bridging platforms for the construction of polynuclear complexes displaying intensive luminescence and/or stimuli-responsive luminescence. ,, In 2019, we presented the synthesis and structure of the hexanuclear copper­(I) complexes containing two Cu 3 I 3 units based on tetradentate N Py ,P,P,N Py -bridging 1,5-diaza-3,7-diphosphacyclooctanes bearing two exocyclic pyridylethyl substituents at the phosphorus atoms. The structure of the obtained complexes was unusual due to the assembly of novel trinuclear copper­(I) moieties stabilized by four donor centers of two ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the low‐energy CT absorption bands, the emission spectra of these complexes do not exhibit red‐shift compared to that of [Cu(Pyim)(POP)](PF 6 ), which may be caused by the interactions between the complexes and PMMA. Four‐coordinate Cu(I) complexes undergo a coordination geometry relaxation at excited state, which leads to the flattening of tetrahedral coordination geometry and decreases the energy level of excited state [13,39–40] . The relaxation can be more impeded in crystal than in PMMA film, thus the emission spectra acquired in PMMA film show obviously red‐shift compared to those acquired in crystal.…”
Section: Resultsmentioning
confidence: 99%
“…Four-coordinate Cu(I) complexes undergo a coordination geometry relaxation at excited state, which leads to the flattening of tetrahedral coordination geometry and decreases the energy level of excited state. [13,[39][40] The relaxation can be more impeded in crystal than in PMMA film, thus the emission spectra acquired in PMMA film show obviously redshift compared to those acquired in crystal.…”
Section: Photoluminescence Performancesmentioning
confidence: 99%